Africa and the Global Economic and Financial Crisis. (1st July 2016) - ,; ,; ,
Abstract : Capitalist economic and financial activities at the metropolitan centers reached the summit, overheated the world economy and exploded in 2007 in the form of economic meltdown. This unfortunate event had severe economic consequences on the world economy which, initially, African economies, being misconstrued as slightly exposed to global financial system, were thought to be the exceptions to the economic distress. The unfolding event, however, refuted this assumption owing to the interconnectedness of global economies. The coercive integration of African economies into the international capitalist economic system has meant that they are vulnerable to and more often than not buffeted by economic developments in the capitalist centers. This article examines the gross impact of one such development as the recent global economic recession on dependent economies of Africa, with a view that Africa's economic development and robustness, which could provide the necessary buffer against externally induced economic distress, are achievable only through self-diversification and industrialization.